2009
DOI: 10.4314/njps.v24i1.46374
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Nicotine Administration On Weight And Histology Of Some Vital Visceral Organs In Female Albino Rats

Abstract: Summary: It has been emphasized that cigarette smoking is not always synonymous with nicotine administration but the toxic effect of cigarette has often been associated with the nicotine content in cigarette. Epidemiologic studies have clearly indicated that cigarette smoking have many deleterious effects on visceral tissues in women. However it is not certain whether this effect is produced entirely by nicotine as cigarettes contain other toxic substances. Using an animal model the direct effect of nicotine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 18 publications
7
30
0
2
Order By: Relevance
“…Histological analysis of liver, kidney and spleen of each experimental group was performed by the method of Iranloye and Bolarinwa [17] . The tissues that were perfused in saline and formalin were fixed for 7 days in 10% formaldehyde after which dehydration was carried out in ascending grade of alcohol.…”
Section: Histological Evaluationmentioning
confidence: 99%
“…Histological analysis of liver, kidney and spleen of each experimental group was performed by the method of Iranloye and Bolarinwa [17] . The tissues that were perfused in saline and formalin were fixed for 7 days in 10% formaldehyde after which dehydration was carried out in ascending grade of alcohol.…”
Section: Histological Evaluationmentioning
confidence: 99%
“…Nicotine worsens liver fibrosis largely in chronic liver disease patients (Soeda et al 2012). Weights of the liver increased to 60 days treatment of nicotine with the appearance of cartilaginous cells in the heart and deposition of adipose around the portal vein in the liver (Iranloye and Bolarinwa 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This finding was supported by a previous study that indicated that nicotine induced accumulation of lipid droplets in zona fasciculata cells that resulted in an increase in adrenal weight. 8,27 Regarding histopathological changes due to nicotine exposure, zona fasciculata cells showed swelling, cytoplasmic degeneration with increased lipid contents. These changes explained the significant increase in the total adrenal cortical thickness and zona fasciculata thickness in this study.…”
Section: Discussionmentioning
confidence: 99%